Draft Eighth Five Year Plan (1990-95) Volume-III Details of Schemes Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1990)
The territory of A & N Islands has been declared of educationally backward. Proper attention for the children right from the inception is therefore essential. Such case is more essential for the weaker sections of the Society. Early childhood care programme is in fact a feeder and support programme for Primary Education. the Programme concentrates on the development of the Child-Physical, Motor, Cognitive, language, emotional, social and moral. Three R Should be introduced at the initial stage. Since the Scheme is meant for Children since inception, mother care is also a part of the programme.
Andaman and Nicobar Administration